Always at the Bottom: Ideologies in Assessment of Emergent Bilinguals. (December 2021) - Ascenzi-Moreno, Laura; Seltzer, Kate
Recent scholarship has identified how the reading assessment process can be improved by adapting to and accounting for emergent bilinguals' multilingual resources. While this work provides guidance about how teachers can take this approach within their assessment practices, this article strengthens and builds on this scholarship by combining translanguaging and raciolinguistic lenses to examine the ideologies that circulate through assessment. By comparing interview data from English as a new language and dual-language bilingual teachers, we found that while reading assessments fail to capture the complexity of all emergent bilinguals' reading abilities, they particularly marginalize emergent bilinguals of color. Thus, we expose the myths of neutrality and validity around reading assessment and demonstrate how they are linked to ideologies about race and language. We offer a critical translingual approach to professional learning that encourages teachers to grapple with these ideologies and shift toward a more critical implementation of reading assessments.